Overview of the SPARC physics basis towards the exploration of burning-plasma regimes in high-field, compact tokamaks. (1st September 2022) - Rodriguez-Fernandez, P.; Creely, A.J.; Greenwald, M.J.; Brunner, D.; Ballinger, S.B.; Chrobak, C.P.; Garnier, D.T.; Granetz, R.; Hartwig, Z.S.; Howard, N.T.; Hughes, J.W.; Irby, J.H.; et al.
Abstract: The SPARC tokamak project, currently in engineering design, aims to achieve breakeven and burning plasma conditions in a compact device, thanks to new developments in high-temperature superconductor technology. With a magnetic field of 12.2 T on axis and 8.7 MA of plasma current, SPARC is predicted to produce 140 MW of fusion power with a plasma gain of Q ≈ 11, providing ample margin with respect to its mission of Q > 2. All tokamak systems are being designed to produce this landmark plasma discharge, thus enabling the study of burning plasma physics and tokamak operations in reactor relevant conditions to pave the way for the design and construction of a compact, high-field fusion power plant. Construction of SPARC is planned to begin by mid-2021.